Pengaruh Debt to Assets Ratio, Debt to Equity Ratio, dan Current Ratio Terhadap Harga Saham PT Polychem Indonesia Tbk Pada Periode 2010-2024 Shinta Shintia Dewi, Fazhar Sumantri, Theysa - Dewi, Shinta Shintia; Sumantri, Fazhar; Pratiwi, Theysa Sahlani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Debt to Assets Ratio. shows the measure used in analyzing financial reports to show the amount of collateral available to creditors. Debt to Equity Ratio Ratio shows the measurement of a company's ability to pay debts with its own capital. Current Ratio shows the ratio to measure the company's ability to pay short-term obligations, the aim of  study is to determine the influence Debt to Assets Ratio, Debt to Equity Ratio, and Current Ratio on the Share Price of PT Polychem Indonesia Tbk During the Period 2010-2014. The type of research data used is a comparative casual approach, or quantitative research with a multiple linear regression model data analysis method and the data is processed using SPSS version 27. The sample collection technique used is Purposive Sampling using a saturated sample of 15 years of the Annual Reports of PT Polychem Indonesia Tbk. The data source used is secondary data used, literature studies through journal. The research result Debt to Assets Ratio calculated t-value 0.806 2.201 with a significant value  of 0.437 0.05 does not have a significant partial effect on stock prices, Debt to Equity Ratio t-value -0.169 2.201 with a significant value  of 0.869 0.05 does not have a significant partial effect on stock prices , Current Ratio t-value 0.464 2.201 with a significant value  of 0.651 0.05 does not have a significant partial effect on stock prices